Design of indoor test-rig to measure dynamic forces and moments on tire contact path of family car - Bukhari M. Kasim; Ilyas Yusuf; Mawardi Mawardi (Politeknik Negeri Lhokseumawe, 2020)
The vehicle's suspension system is designed to absorb shocks from road disturbance. The dynamic behavior of a tire suspension depends on many factors. Some main factors are vehicle load, speed, steering angle, road disturbances and the amount of tire elasticity. The dynamic behaviour of the tire is very difficult to observe when the vehicle is traveling on the road. To overcome this problem, in this paper, a test rig will be designed to be able to observe changes in tire dynamic properties experimentally for family car type. The design concept is based on the sprung and un-sprung mass dynamics. This research was conducted by five methods; study mechanism of measuring the tire dynamic behaviors, design of test equipment construction, simulations, and analysis of construction strength. The spring mass construction is designed to have 1 degree of freedom which is able to move the translation in a vertical direction to indicate changes in car body height. On the other hand, the un-sprung mass construction is designed to have 3 degrees of freedom that can move translation in the vertical direction, rotation in the z axis and rotation in the x axis. Movement in the vertical direction is to simulate a tire jump, rotation on the z axis is to simulate the steering angle and rotation on the x axis is to simulate the camber angle. The design result shows that the design construction not only saves to handle all forces and moments but can also fulfill functions to simulate the dynamic response of the car model. Simulation result shows maximum stress is point on C-D bar that is 7.13 N/mm2. This value is less than allowable shear stress which is 37N/mm2. By all simulation result, it can be concluded that all materials used are saved for this construction.